Quantification of parasite burden of Trypanosoma cruzi and identification of Discrete Typing Units (DTUs) in blood samples of Latin American immigrants residing in Barcelona, Spain - Tavares de Oliveira, Maykon; Sulleiro, Elena; Silgado Gimenez, Aroa; de Lana, Marta; Zingales, Bianca; Santana da Silva, João; Marin-Neto, J. Antônio; Molina, Israel (PLOS Neglected Tropical Diseases, 2020)
Author summary Trypanosoma cruzi is divided in seven distinct genetic groups (TcI-TcVI) and TcBat. They can be related to several biological parameters, the main being resistance to specific treatment. Due to the intense migration movements, ChD has become a serious public health problem in Europe. Thus, the work has the important function of identifying the genetic variability of T. cruzi circulating in the European continent, in addition to assessing the parasitic burden present in 101 chronic chagasic patients, residing in Barcelona, Spain. We show differences in the predominance between the infecting DTUs among Bolivian (TcV) and non-Bolivian patients (TcII/TcVI). This is the first study to describe the presence of TcVI genotype in Europe. Although the level of parasite burden is low/medium, it is higher in patients from Bolivia when compared with patients of other countries. The low parasitic burden is a limitation factor for studies aimed at evaluating by qPCR the effects of treating this disease with the drugs available to date, Benznidazole and Nifurtimox, and for clinical trials of new drugs. The information generated in this study should impact planning of more effective public health interventions to improve the health of chagasic patients, control vertical transmission and treatment of ChD.